On dimension-free integrability improvement for Sobolev embeddings - Krbec, Miroslav (Eurasian Mathematical Journal, 2013)
We survey recent dimension-invariant embedding theorems for Sobolev spaces, focusing on the behavior of embedding constants with respect to the dimension.